2007
DOI: 10.1007/s11906-007-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the electrophysiology of brainstem circuits controlling blood pressure

Abstract: The brainstem contains the necessary circuitry for the maintenance and regulation of arterial blood pressure. It has become increasingly clear in the past few years that the characteristics of the neurons that constitute these circuits are not static, but can be altered in the face of chronic changes in physiological state. Alterations in voltage-gated and ligand-gated ion channels have been reported in neurons located within the nucleus of the solitary tract and the nucleus ambiguus in response to hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The effect of TRIM suggests that nNOS contributes to ACh-induced cardiovascular responses. Similar effects of L-NAME and TRIM on glutamatergic transmission were previously observed in modulation of NTS neurons discharge (10,24). A study by Scislo et al (33) reported that L-NAME and TRIM are equipotent in inhibiting cardiovascular responses elicited by the stimulation of adenosine A2a receptors in the NTS.…”
Section: Discussionsupporting
confidence: 62%
“…The effect of TRIM suggests that nNOS contributes to ACh-induced cardiovascular responses. Similar effects of L-NAME and TRIM on glutamatergic transmission were previously observed in modulation of NTS neurons discharge (10,24). A study by Scislo et al (33) reported that L-NAME and TRIM are equipotent in inhibiting cardiovascular responses elicited by the stimulation of adenosine A2a receptors in the NTS.…”
Section: Discussionsupporting
confidence: 62%
“…20 Alternatively, the lowering of the arterial pressure could depend on central effects of the hypoxia on the center of the arterial pressure regulation. 21 However, the effects of hypoxia on blood pressure are believed to result in sympathetic activity increase, leading to upregulation of blood pressure and heart rate. 22 Our results also show that hypoxia did not affect cardiac output but decreased TPR and subsequently blood pressure levels.…”
Section: Discussionmentioning
confidence: 99%